ANALISIS SOAL MATA PELAJARAN PPKN PADA BUKU SISWA KELAS VI DITINJAU DARI PENGEMBANGAN HOTS - Muthia Saridewi; Dinie Anggraeni Dewi; Yayang Furi Furnamasari (Universitas Tanjungpura, 2022)
This research is motivated by the demands in education that require to be able to provide learning oriented to higher order thinking skills (HOTS), and the demands of students who must have attitudes, knowledge and skills in reflecting Pancasila students who are able to practice Pancasila values. The learning process in elementary schools is supported by students' thematic books as a support for the learning process activities, in the thematic books used there are test questions and assignments as an effort to hone the thinking process and determine the achievement of students' knowledge. This study aims to find out the PPKN material test questions in the sixth grade elementary school students' books containing the Higher Order Thinking Skill (HOTS) dimensions of cognitive processes of analyzing (C4), evaluating (C5), and creating (C6). This research method uses a qualitative approach with the method of content analysis or content analysis. The data source for this research is the thematic book for grade VI elementary school students, themes 1 to 9, published by the Ministry of Education and Culture in the revised edition of 2018. The data collection technique uses documentation studies, literature studies, and content analysis in terms of HOTS indicators. Based on the results of the study, the test questions in the thematic books for sixth grade elementary school students already contain questions that develop the cognitive aspects of the HOTS dimension in the cognitive processes of analyzing (C4), evaluating (C5), and creating (C6).